The role of histone modification and a regulatory single-nucleotide polymorphism (rs2071166) in the Cx43 promoter in patients with TOF - Gu, Ruoyi (Sci Rep, 2017)
Abnormal level of Cx43 expression could result in CHD. Epigenetic modification and disease-associated, non-coding SNPs might influence gene transcription and expression. Our study aimed to determine the role of histone modification and an rSNP (rs2071166) in the Cx43 promoter in patients with TOF. Our results indicate that H3K18ac bind to Cx43 promoter and that their levels are reduced in TOF patients relative to controls. The relationship between the non-coding SNP in the Cx43 gene and TOF patients was evaluated in 158 patients and 300 controls. The C allele of rs2071166 was confirmed to result in an increased risk of TOF (OR = 1.586, 95%CI 1.149–2.189). Individuals with the CC genotype at rs2071166 also showed a significant susceptibility to TOF (OR = 2.961, 95%CI 1.452–6.038). The mRNA level in TOF who were CC genotype was lower than that in patients with the AA/AC genotype. Functional analysis in cells and transgenic zebrafish models showed that rs2071166 decreased the activity of the promoter and could block the interaction between RXRα and RARE. This is the first study to illustrate that epigenetic modification and an rSNP in the Cx43 promoter region play a critical role in TOF by impacting the transcriptional activity and expression level of Cx43.